Image-Guided Radiotherapy for Locally Advanced Head and Neck Cancer - Nguyen, Nam P.; Kratz, Sarah; Lemanski, Claire; Vock, Jacqueline; Vinh-Hung, Vincent; Gorobets, Olena; Chi, Alexander; Almeida, Fabio; Betz, Michael; Khan, Rihan; Godinez, Juan; Karlsson, ULF L.; et al. (Frontiers in Oncology, 2013)
Treatment of locally advanced head and neck cancer remains a challenge because of the head and neck complex anatomy and the tumor invasion to the adjacent organs and/or metastases to the cervical nodes. Postoperative irradiation or concurrent chemoradiation may lead to damage of radiosensitive structures such as the salivary glands, mandible, cochlea, larynx, and pharyngeal muscles. Xerostomia, osteoradionecrosis, deafness, hoarseness of the voice, dysphagia, and aspiration remain serious complications of head and neck irradiation and impair patient quality of life. Intensity-modulated and image-guided radiotherapy by virtue of steep dose gradient and daily imaging may allow for decreased radiation of the organs at risk for complication while preserving loco-regional control.